A model and empirical test of evolving consumer perceived brand innovativeness and its two-way relationship with consumer perceived product innovativeness. Issue 4 (November 2020) - Shams, Rahil; Brown, Mark; Alpert, Frank
Highlights: Existing brand innovativeness perceptions influence perceived product innovativeness. Technological newness has a strong influence on perceived product innovativeness. Perceived product innovativeness leads to updating of perceived brand innovativeness. Brand innovativeness directly influences brand attitude and purchase intention. It mediates the effect of product innovativeness on attitude and purchase intention. Abstract: This paper examines the evolution of consumer perceived brand innovativeness through its relationship with product innovativeness. A survey of 617 respondents measured consumer perceptions, brand attitude, and purchase intention, with data analysed using structural equation modelling. Results indicate that after exposure to a product innovation, consumers' existing perception of brand innovativeness and perception of the technological newness of the innovation shape their perception of product innovativeness. This leads to an updating of perceptions of innovativeness at the brand level, which subsequently influence both brand attitude and purchase intention outcomes. It also mediates the impact of product innovativeness on these variables. This model of the evolution of brand innovativeness shows how it can be strengthened (or weakened) by product innovativeness. A key managerial implication is that investment and production of highly innovative products will result in a virtuous cycle of increasing future perceptions of product and brand innovativeness. Chinese Abstract: 本文通过消费者感知品牌创新力与产品创新力的关系来考察消费者感知品牌创新力的演变过程.本文开展了一项针对617名受访者的调查并测量了消费者的感知, 品牌态度和购买意愿, 并使用结构方程模型对数据进行分析.结果表明, 消费者在接触产品创新后, 对品牌创新的现有感知和对创新的技术新颖性的感知形成了对产品创新的感知.这导致了品牌层面对创新认知的更新, 进而影响了品牌态度和购买意图的结果.它还中介了产品创新性对这些变量的影响.这个品牌创新力演化模型显示了产品创新力是如何增强 (或减弱) 品牌创新力的.从本研究可以得出一个重要的管理意义, 即高创新产品的投资和生产将促进消费者未来对该产品和品牌创新的认知不断增强的良性循环.